Spectrum of pediatric malignancy- A cancer hospital-based study - Gupta, Vidhi; Kalraiya, Ashish; Mekle, Dinesh (Pediatric Review: International Journal of Pediatric Research, 2020)
Objective: Childhood malignancy being a significant cause of mortality among children. The aim of the study is to find out the epidemiology of tumours in children in our region below <14 years age who presented to tertiary care Cancer hospital, Bhopal, M.P. for period of four years (2015- 2018). Methodology: All children with cancer, aged 1-14 years diagnosed by mean of histological and cytological examination during a period of 4 years were reviewed. Results: During the period of four years 275 patients were diagnosed as having paediatric malignancies. According to year wise distribution highest incidence of cases were found in 2016 (32.72%). The highest number of cases, 96(35%) were in 10-14 years of age group and mean age was 7.43 with SD 4.0. Male were affected more than females with ratio of 2.66:1. It was observed that haematological malignancies were more common 172(62.54%) than the non haematological malignancies 103(37.45%). Leukemia 150 (54.54%) is most common pediatric cancer amongst which Acute lymphoblastic leukemia is most common haematological malignancy. Overall, it was found that most common cancer group in the present study were leukemia (54%) followed by lymphoma (8.36%), Brain tumours (7.27%) and Sarcoma (7.27%). Conclusion: Although the exact incidence rate cannot be provided by this hospital-based study, the information is useful in showing distribution patterns of childhood malignancy in this region.